Effects of ethylene, cytokinin, and physical treatments on BoPaO gene expression of harvested broccoli. - Gómez Lobato, María Eugenia (2011)
BACKGROUND: Broccoli is a highly perishable vegetable that shows enhanced postharvest senescence and intense de‐greening caused by chlorophyll degradation. One of the key steps of chlorophyll catabolism is the opening of chlorophyll tretrapyrrole catalysed by pheophorbide a oxygenase (PaO). In this study the expression of a gene encoding a putative PaO was characterised under several chemical and physical treatments. RESULTS: A fragment of a gene encoding a PaO from broccoli (BoPaO) was cloned. The expression of BoPaO showed an important increment during postharvest senescence, in correlation with chlorophyll degradation. Furthermore, broccoli heads were treated with the hormones cytokinin and ethylene. Cytokinin delayed the increment in BoPaO expression, while ethylene accelerated the process. Also, several postharvest treatments were applied in order to evaluate their effect on BoPaO expression. Samples treated with modified atmosphere, hot air, UV‐C or white light showed a delay in chlorophyll degradation and de‐greening. In most cases the treatments also delayed the increment in BoPaO expression during senescence. CONCLUSION: A close correlation between chlorophyll degradation and BoPaO expression was found during broccoli senescence. This relationship was corroborated in samples treated with different hormonal and physical applications. Copyright © 2011 Society of Chemical Industry